Effectiveness of Immunosuppressive Therapy in Children with IgA Nephropathy (Herald of the National Children's Medical Center, 2025)
Study of the outcomes of treatment with prednisolone monotherapy and other immunosuppressive drugs in children with IgA nephropathy.
Keywords: IgA nephropathy; children; immunosuppressive therapy; prednisolone; kidney function